Decolonizing road safety for transportation justice in Australia. (September 2021) - Johansen, Nadia; Wilson, Rohan; Tichon, Jennifer; Senserrick, Teresa; Tranter, Kieran
Highlights: Decolonizing road safety is needed for transport justice for First Nations peoples. Decolonized road safety acknowledges the trauma of colonialism. Decolonized road safety adopts First Nations research methods. First Nation research methods empowers and works with First Nations people. Yarning is method particularly suited to decolonizing Australian road safety. Abstract: Australia has a fundamental, deep, and enduring transport injustice. First Nations people endure road deaths and injury figures at vastly higher rates than the figure for non-First Nations people, suggesting that road safety research has not translated into successful policies and programs that sustainably reduce First Nations road trauma. In this paper, we argue that the decolonization of road safety research can only occur with First Nations people using culturally appropriate methodologies. We evaluate the scope and possibility of First Nations methodologies for decolonizing road safety, finding that yarning, or the ubiquitous use of conversation and storytelling to generate, pass on, and exchange knowledge, is a promising research methodology for decolonizing Australian road safety.